In-Hospital complications of Q wave acute myocardial infarction at the department of cardiology of the hospital "Edgardo Rebagliati Martins". 1989-1993 - Pariona, Marcos (1996)
Myocardial infarction is one the most important causes of admission and death at the Department of Cardiology of "Edgardo Rebagliati Martins" Hospital. This study reviews the complications of 536 patients admitted to our deoartment with the diagnosis of Q wave acute myocardial infarction from 1989 to 1993. Out of these, 234 patients (43.6%) had a complication, in 45 cases it was fatal, and total mortality was 8,4%. Pump failure was the most frequent complication, occurred in 106 cases (19,7%), and turned to cardiogenic shock in 28 patients (5,2%). Sinus tachycardia was the most frequent arrhytmia, in 152 cases (28,3%), followed by sinus bradycardia with 88 cases (16,4%), premature ventricular contractions in 58 cases (10,8%), atrial fibrillation in 40 cases (7,5%) and ventricular tachycardia and ventricular fibrillation in 8 (1,5%) and 9 cases (1,6%) respectively. Is at this paper "quantifies" complications and mortality from myocardial infarctation at our hospital in order to improve resources distribution in the control of this illness.